(untitled) (Research, Society and Development, 2020)
Klebsiella pneumoniae is an important opportunistic pathogen responsible for considerable rates of nosocomial infections. In addition, this species is an important source of antibiotic resistance, presenting a great capacity to acquire plasmids with genes that give them resistance to multiple antibacterials, which makes it necessary to develop therapeutic alternatives. The combination of phytochemicals and classic drugs has been shown to be beneficial. Based on this, this study aimed to investigate the potential use of carvacrol in combination with the antibacterials classically used in clinical practice ceftazidime and cefepime, in order to optimize the treatment of these infections. The association was carried out using the checkerboard method. The observed result for 100% of the strains analyzed was an additive effect in the combination of carvacrol with ceftazidime and carvacrol with cefepime. Thus, carvacrol has potential use as an adjunct in the treatment of infections caused by K. pneumoniae in combination with ceftazidime and cefepime, due to the additive effect shown in the combination with both drugs. Structural changes can be made to improve this observed effect. This research opens perspectives for more studies that aim to analyze the effects of the combination of carvacrol with other antibacterial drugs.